Human rights theory and practice - Goodhart, Michael E. 1969- (New York, NY Oxford University Press, 2023)
Human Rights: Theory and Practice is a comprehensive, interdisciplinary text written by a global team of experts with coverage and content unrivaled by any other text on the market. With contributions from an international panel of experts, including political scientists, lawyers, philosophers, and policy-makers, this text is unmatched in its ability to provide students with a practical, comprehensive and 21st century perspectives on the theory, study and practice of human rights"--
Introduction / Michael Goodhart -- The philosophical foundations of human rights / Anthony Langlois -- Human rights in international law / Rhona Smith -- The politics of human rights / Michael Goodhart -- Feminist approaches to human rights / Laura Parisi -- Imperialism and human rights / Bonny Ibhawoh -- The social life of human rights / Damien Short -- Human rights claiming as a performative practice / Karen Zivi -- Genocide / Scott Straus -- Humanitarian intervention / Alan Kuperman -- Transitional justice / Joanna Quinn -- Treaties, monitoring, and enforcement / Emily Ritter -- Political democracy and state repression / Christian Davenport -- Migration and refugees / Gil Loescher & Kurt Mills -- Human rights and the environment / Sumudu Atapattu -- Indigenous rights and language sovereignty / Odilia Romero, Joseph Berra, & Shannon Speed -- Social movements and human rights / Jackie Smith -- Theory in practice : making human rights claims in a human rights way / Brooke Ackerly -- Sexual orientation, gender identity, and human rights / Cricket Keating and Cindy Burack -- Religion and human rights / Roja Fazaeli and Joel Hanisek -- The human right to water / Madeline Baer -- The SDGs and economic rights / Inga Winkler & Matheus de Carvalho Hernandez.
Includes bibliographical references and index.
Keywords: Human rights -- Textbooks